Prevalent User-centered Monetization Techniques in Social Media - Bruce, Mark Rowland; Adekoya, Adebayo Felix; Boateng , Samuel; Appiahene, Peter (International Review of Management and Marketing, 2023)
This study provides a solid illustration of the degree to which social media sites are now incorporated into market research. Several studies have explored the impact of the continual connection between customers and companies on the social web platforms, with direct connotation for the enhancement of new products and trading. The effect of user and content market-production for participation on social web platform line communities on purchase expenditures is positive. There is a specific connection between increasing social media interaction and improved customer participation and loyalty. It has been discovered that blogs aid managers in the screening phase of product development and give power for negotiating better contract conditions. The aim of the paper was to review relevant literature on user-centered monetization techniques in social media. The study employed prisma analysis for this review. During the study, the main social media monetization techniques that were found were sponsorship, advertisement, public relations, affiliate, ambassadors and crowd funding.